2022
DOI: 10.1093/eurpub/ckac037
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and protective factors in adults with and without diabetes mellitus (Italy, 2016–19)

Abstract: Background Cardiovascular (CV) diseases are a major cause of the disease burden worldwide and contribute substantially to health care costs, in particular in people with diabetes. Their incidence can be reduced by multi-factorial interventions. This study intends to describe the occurrence of CV risk and protective/preventive factors in the adult population resident in Italy, to better target public health interventions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, a retrospective study reported that pre-transplant diabetes mellitus could increase the risk of cancer after LTx, and cancer is a major source of morbidity and mortality in patients with solid organ transplantations [ 23 ]. To our knowledge, diabetes also increases the morbidity of cardiovascular diseases, which are thought to increase the mortality of patients receiving LTx [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a retrospective study reported that pre-transplant diabetes mellitus could increase the risk of cancer after LTx, and cancer is a major source of morbidity and mortality in patients with solid organ transplantations [ 23 ]. To our knowledge, diabetes also increases the morbidity of cardiovascular diseases, which are thought to increase the mortality of patients receiving LTx [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%